2013
DOI: 10.3109/14767058.2013.784740
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ultrasonography and magnetic resonance imaging in pregnant women at risk for placenta accreta

Abstract: US and MRI were useful in the diagnosis of placenta accreta with lacunae and an abnormal color Doppler imaging pattern are the most helpful findings. MRI is most clearly indicated when US findings are ambiguous or there is a posterior placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 25 publications
1
56
0
1
Order By: Relevance
“…La resonancia magnética (RM) puede definir el compromiso uterino y de los órganos vecinos (11,20). Los hallazgos específicos en RM son: abombamiento del útero, placenta de intensidad de señal heterogénea y bandas gruesas intraplacentarias hipointensas en las imágenes potenciadas en T2 (11,15).…”
Section: Resultsunclassified
“…La resonancia magnética (RM) puede definir el compromiso uterino y de los órganos vecinos (11,20). Los hallazgos específicos en RM son: abombamiento del útero, placenta de intensidad de señal heterogénea y bandas gruesas intraplacentarias hipointensas en las imágenes potenciadas en T2 (11,15).…”
Section: Resultsunclassified
“…In our case, these features were visualized at 13 weeks and became more pronounced in the second trimester. According to Elhawary et al [22], the sensitivity and specificity of ultrasound to detect placenta accreta are 82.0% and 89.6%, respectively, while the positive and negative predictive values were 72.7% and 92.8% despite a relatively small sample size ( n = 39). However, Dwyer et al [3] had a similar sample size ( n = 32) and reported 93% sensitivity and 71% specificity in identifying placenta accreta.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of placenta accreta, increased vascularization of the placental-myometrial interface is an indication of an abnormality [23]. According to Elhawary et al [22], an abnormal color Doppler imaging pattern is a helpful finding for identification of placenta accreta. The most common findings identified by color Doppler are placental lacunae with turbulent blood flow and a hypervascular serosa-bladder interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several reports of placental abnormalities defined by MRI have appeared [33,34]. In addition, an increasing number of pregnancies are complicated by placental adhesive disorder, and clinicians are requesting imaging for the diagnosis and to aid surgical planning [35,36].…”
Section: The Placentamentioning
confidence: 99%